Symbolic Interpretation of Pantang Larang in Matalibaq Village East Kalimantan - Dewi, Suci Mutiara (Universitas PGRI Adi Buana Surabaya, 2025)
This research discusses about pantang larang in Matalibaq Village. Long Hubung District, Mahakam Ulu Regency, East Kalimantan. There are several pantang larang that have become cultural traditions in the village of Matalibaq which are currently believed by local residents. Pantang larang becomes an icon in Matalibaq culture when there are newcomers who are visiting. This research will highlight how the forms of pantang larang that occur in Matalibaq Village use a literary anthropology approach by highlighting the symbolic interpretation of Clifford Greetz. The research method in this research is qualitative method. The data source of this research is an interview with a source person who comes from the original Matalibaq village. The results of this study suggest that there are 6 pantang larang, namely, 1) excuse me, 2) raise a child, 3) musib month, 4) traditional marriage, and 5) not allowed to overdo it with animals. All five of these pantang larang’s have the same consequences when disregarded, namely misfortune, disasters, unhappiness, poverty, illness, discomfort, and so on. Adherence to traditional customs is important to achieve balance in daily life.